Effect of pre-treatment on catalytic coal gasification characteristics of sub-bituminous coal. (June 2021) - Lu, Tao; Mao, Yandong; Wang, Huifang; Liu, Lei; Li, Kezhong
Abstract: Sintering or agglomeration is formed in the process of the gasification of coal when fluxing K2 CO3, which leading to the entire bed defluidization. In order to study the catalytic coal gasification reactivity and agglomeration properties in pressurized fluidized bed, Wangjiata raw coal, demineralized coal with HCl-HF treatment, and raw coal with different amounts of clay mineral addition were selected. The catalytic coal gasification reactivity, the agglomeration and sintering properties were studied. As well as water-soluble catalyst recovery from the gasification residue was also determined. The results show that for potassium-catalyzed steam gasification, not only coal ash content but also composition affected the gasification reactivity, agglomeration, and catalyst recovery. The carbon conversion increased varying degrees with increasing K2 CO3 loadings, K2 CO3 impregnated coal showed a high degree of agglomeration, and agglomeration increased with increasing K2 CO3 amount. Demineralized coal couldn't improve the agglomeration property. The addition of Clay mineral, was found to be very efficient in anti-sintering. However, compared with demineralized coal, the carbon conversion and water washing catalyst recoveries decreased obviously for those samples with the addition of clay minerals. The test verifies that part of potassium catalyst irreversibly reacted with coal ash to form relatively water-insoluble potassium compounds such as kaliophilite and sanidine. Highlights: Not only ash composition but also content of the ash affects gasification reactivity, agglomeration and catalyst recovery. The addition of Clay mineral, was very efficient in anti-sintering in the pressurized bed gasifier. The presence of KOH phase appears responsible for the agglomeration in the catalytic coal gasification gasifier. Loading 15 wt% K2 CO3 and 5 wt% clay mineral can solve the agglomeration problem without reduce carbon conversion obviously.